Analysis of Language Errors in Comments on Social Media Twitter Account @Tanyarl (Pragmatic Studies) - Siti Hasna Ummu Hani; Intan Sari Ramdhani (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This research is a descriptive qualitative research with library study data collection techniques. The subject of this research is comments on the @tanyarl account comment column. The @tanyarl account is an account with thousands of followers and has many opportunities for their tweets to go viral. One of the factors is because it contains topics that are currently being discussed or contains pros and cons that provoke a lot of comments from netizens. From several comments, it was found that comments violated the principle of cooperation in communication, so that the purpose of communication was not achieved and the communication did not go well. Based on the findings, the data found were 20 data on violations of the principle of cooperation with details of 6 data on violations of the maxim of quantity, 4 data on violations of the maxim of quality, 8 data on violations of the maxim of relation, and 2 data on violations of the maxim of manner. Violation of the principle of cooperation can also occur due to a person's habits, culture and character so that it is carried over to the social media comment column. This explanation can be a reflection to adhere to the principles of cooperation so as to minimize misunderstandings in communication.